Freezing the Dynamic Gap for Selectivity: Motion‐Based Design of Inhibitors of the Shikimate Kinase Enzyme. Issue 50 (4th October 2016) - Prado, Verónica; Lence, Emilio; Thompson, Paul; Hawkins, Alastair R.; González‐Bello, Concepción
Abstract: Shikimate kinase (SK), the fifth enzyme of the aromatic amino acid biosynthesis, is a recognized target for antibiotic drug discovery. The potential of the distinct dynamic apolar gap, which isolates the natural substrate from the solvent environment for catalysis, and the motion of Mycobacterium tuberculosis and Helicobacter pylori SK enzymes, which was observed by molecular dynamics simulations, was explored for inhibition selectivity. The results of the biochemical and computational studies reveal that the incorporation of bulky groups at position C5 of 5‐aminoshikimic acid and the natural substrate enhances the selectivity for the H. pylori enzyme due to key motion differences in the shikimic acid binding domain (mainly helix α5). These studies show that the less‐exploited motion‐based design approach not only is an alternative strategy for the development of competitive inhibitors, but could also be a way to achieve selectivity against a particular enzyme among its homologues. Abstract : Enzyme dynamics : The asynchronous and more limited opening and more parsimonious motion of the shikimic acid domain of the Helicobacter pylori enzyme during catalytic turnover were exploited for the design of selective inhibitors (see figure).